Histopathological study of placenta in association with deranged thyroid profile,in known case of pre-eclampsia/eclampsia - Sangeeta Hudda; Anubha Choudhary (Tropical Journal of Pathology and Microbiology, 2022)
Objectives: To assess the histo-morphology of the placenta in association with abnormal thyroidhormone levels in patients with Pre-eclampsia/Eclampsia, concerning the birth weight of the baby.Methods: The study was performed in the department of Pathology over 3 months. Cases andcontrols were evaluated based on the 3rd trimester TSH level of the Antenatal patients. Cases wereconsidered as patients who had levels of TSH outside the normal range in the 3rd trimester (0.3-3.1mIU/L). Out of 50 patients,15 cases and 33 controls were defined. A histopathological report ofthe resected placenta specimens was received. Clinical details of the mother and the birth weight ofthe baby were collected. Finally, the correlation between placental histo-morphology, mother'sdiagnosis and baby birth weight were correlated.Results: Among all the cases, 9 patients (60%)were diagnosed with pre-eclampsia, as compared to 4 (14.8%) among controls. Concerninghistology, hemorrhage in the placenta was observed more among the cases (13/15; 86.6%) ascompared to controls (51.8%). Calcification was more among the controls (55.5% vs 26.6%).Among other characteristics like placental weight, infarction, chorangiosis, syncytial knots andvillitis, no significant difference was noted. 58.8% (10/17) of babies born to cases had Low birthweight (<2.5 kg) compared to 40.7% in controls.Conclusion: The occurrence of pre-eclampsia washigh among mothers with abnormal thyroid hormone levels. Similar observations were seen in theincreased incidence of low birth weight babies. So, we strongly recommend performing thyroidscreening on all ANC patients.